Job differences in perceived occupational stress among University of Ibadan workers (2004)
The study examined job differences in perceived occupational stress among University of Ibadan workers. Two hundred and eighty (280) participants were selected from the population of employees of the university. They responded to a stress scale developed/or the study. The Expost facto research design was adopted. Three hypotheses generated in the study were tested using appropriate statistical tools. Results obtained showed that. Academic Staff experienced higher level of stress than the non-academic staff On the contrary, gender did not significantly influence the workers 'perceived level of stress. The long serving employees experienced lower level of stress than the newer members of staff Conclusions were drawn and recommendations made bused on the findings